Analisis Pemaknaan Warna Lampu Lalu lintas sebagai Komunikasi Nonverbal Bagi Pengendara Motor Dikabupaten Bone - Elisdayanti; Suci Rahayu; Mus Muliadi; Kurniati Abidin (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
This study aims to analyze the meaning of traffic colors as nonverbal communication for motorcyclists in Bone Regency. The approach used is descriptive qualitative with a semiotic method, namely studying signs and how these signs produce meaning in the communication process. Data were obtained through in-depth interviews with two motorcyclists in Bone Regency. The results of the study indicate that the meaning of traffic light colors for each motorcyclist in Bone Regency with the aim of the study to reveal the level of understanding, attitudes, and behavior of drivers in responding to nonverbal messages conveyed by traffic lights, this study emphasizes that traffic lights are not just physical devices, but a sign system whose meaning must be understood and interpreted correctly by the community. Non-compliance with this sign indicates a shift or difference in interpretation in society, which can endanger mutual safety.